Design Of An Attendance Application System Using Face Recognition And Location Based On Android - Ainun Rizkyani Fadillah; Jalil, Abdul (Information Technology International Journal, 2024)
This research presents the design of an attendance application using face recognition and location technology for CV. Waysolve. The aim is to improve the efficiency, accuracy, and security of employee attendance compared to traditional methods. The study begins with an analysis of the current attendance system to identify issues such as data inaccuracies and fraud potential. Utilizing advanced technologies like face recognition algorithms and GPS, the proposed system streamlines attendance processes. The design phase employs Use Case Diagrams and Class Diagrams to define functional requirements and database structure, while a client-server architecture ensures clear separation between user interface and business logic, enhancing security. Incorporating Object-Oriented Programming (OOP) and functional programming paradigms results in clean, maintainable code. The successful implementation of this system is expected to improve employee productivity, accountability, and data accuracy, providing a solid foundation for future developments in attendance management.